Key Trends in the Implementation of the Fund's Transparency Policy. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
At the time of the 2005 review of the Fund's transparency policy, it was agreed that information on key trends in implementation of the transparency policy would be circulated to the Board regularly, along with lists indicating the publication status of reports discussed by the Board. The set of tables provided in this report updates the last Key Trends 2 with information on documents published through December 2007. An update will continue to be issued annually to the Executive Board.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Article IV Board; Country Policy Intention Document; PP; Publication Rate; Staff Report; Mongolia